The Influence of Democratic Leadership Style and Organizational Culture on High School Teachers' Work Motivation - Fitri Rohana; Eka Fitria Ningsih; Agus Setiawan; Subandi Subandi (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the influence of democratic leadership style and organizational culture on high school teachers' work motivation in Sumberejo District, both partially and simultaneously. The research is motivated by the decline in teachers' work motivation due to high workload, the demands of the Merdeka Curriculum implementation, and the suboptimal application of leadership and organizational culture in schools. This study employed a quantitative approach with an associative research design. The population consisted of all high school teachers in Sumberejo District, with a sample of 57 teachers selected using cluster sampling technique. Data were collected through a Likert-scale questionnaire (1–5) that had been tested for validity and reliability. Data analysis techniques included descriptive statistics, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS. The results showed that: (1) democratic leadership style has a positive but not significant effect on teachers' work motivation (t-count = 1.730, sig. = 0.089 > 0.05); (2) organizational culture has a positive and significant effect on teachers' work motivation (t-count = 8.192, sig. = 0.000 < 0.05); (3) simultaneously, democratic leadership style and organizational culture have a significant effect on teachers' work motivation (F-count = 65.744, sig. = 0.000) with a contribution of 70.9% (R² = 0.709). This study concludes that organizational culture is the dominant factor in improving teachers' work motivation, while democratic leadership style alone is not sufficient. Therefore, strengthening organizational culture should be a priority in efforts to enhance teacher motivation and educational quality.